The beneficial effects of honeybee-venom serum on facial wrinkles in humans - Han SM (Dove Medical Press, 2015)
Sang Mi Han,1 In Phyo Hong,1 Soon Ok Woo,1 Sung Nam Chun,2 Kwan Kyu Park,3 Young Mee Nicholls,4 Sok Cheon Pak5 1Department of Agricultural Biology, National Academy of Agricultural Science, Wanju, 2Dong Sung Pharmaceuticals Co Ltd, Seoul, 3Department of Pathology, School of Medicine, Catholic University of Daegu, Daegu, South Korea; 4Manuka Doctor Ltd, Auckland, New Zealand; 5School of Biomedical Sciences, Charles Sturt University, Bathurst, NSW, Australia Abstract: Facial wrinkles are an undesirable outcome caused by extrinsic photodamage and intrinsic aging processes. Currently, no effective strategies are known to prevent facial wrinkles. We assessed the beneficial effects of bee-venom serum on the clinical signs of aging skin. Our results show that bee-venom serum treatment clinically improved facial wrinkles by decreasing total wrinkle area, total wrinkle count, and average wrinkle depth. Therefore, bee-venom serum may be effective for the improvement of skin wrinkles. Keywords: bee venom, wrinkle, area, count, depth